Mustura daral, a new species of stone loach from Arunachal Pradesh, Northeast India (Teleostei: Nemacheilidae) - Rameshori, Yumnam; Chinglemba, Yengkhom; Darshan, Achom; Vishwanath, Waikhom (Zootaxa, 2022)
Mustura daral, new species, is described from the Siang River (Brahmaputra drainage) in Arunachal Pradesh, Northeast India. The new species is distinguished from its congeners by: 9–10 dark-brown saddles on dorsum, each continued down on flank forming regularly set and shaped dark-brown bars; two black blotches at caudal-fin base; caudal fin forked with 9+8 branched rays; lateral line complete; median notch in lower jaw absent; axillary pelvic lobe large; and suborbital flap in male with conspicuous tubercles along posterior rim.